Ujaran Guru dalam Kelas Bahasa Inggris sebagai Penutur Asing dalam Pendekatan Saintifik: Dalam Sudut Pandang Speech Acts - Rihza Galih Faturrochman; Achmad Anang Darmawan; Faishol Hadi (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2021)
This paper reviews teacher’s utterances in the EFL Classroom using Speech Acts’ perspective. Specifically when the teacher applying scientific appraoch in the learning process. Teacher’s utterance has a lot of influence in the language learning process, such as: students’ input and practice (Xiao-yan, 2006) and (Cullen, 1998). Even though the restiction on using scientific approach in all subject has been revoked, some schools still applying scientific approach in EFL Classroom which is relatively unfamiliar. Theoretically, since Indonesia use English as foreign learning, teacher’s utterance has a prominent role in the process of learning in the classroom. In the classroom context, teacher talk can be found in the form of questions and feedback (Cullen, 1998)And (Xiao-yan, 2006). The research had been done using qualitative method, which means the data of the research are analysed using qualitative methods and the result is presented in paragraph. In order to gather the data, observation and interview had been done in the early of 2020. As result, a teacher in MA Bilingual Muslimat NU Sidoarjo uses the directive sentence mostly in the classroom, since she believes that encourage students to speak in English is very necessary for English as foreign language learner.